A case of Ramsay Hunt syndrome diagnosed after kidney transplantation - Yoo Min Park; Da Rae Kim; Ji Yoon Park; Seul Ki Kim; Se Yun Kim; Jin Sug Kim; Yu Ho Lee; Yang-Gyun Kim; Kyung-Hwan Jeong; Ju-Young Moon; Sang-Ho Lee; Chun-Gyoo Ihm; et al. (The Korean Society of Nephrology, 2015)
We report the first case of Ramsay Hunt syndrome (RHS) diagnosed after kidney transplantation in Korea. RHS is a disease caused by latent varicella-zoster characterized to involve geniculate ganglion of the seventh cranial nerve. Patients who have undergone kidney transplantation can be easily affected by viral infections because of their immune-compromised status. A 35-year-old man with hypertensive end-stage renal disease underwent kidney transplantation. Two months after surgery, the recipient was diagnosed with RHS and treated with antivirals and steroids. However, after using the antiviral agents for the recommended duration, facial paralysis occurred as a new presentation and he required further treatment. Otalgia and periauricular vesicles improved, but the facial palsy remained.